Clarifying the effects of environmental factors and fishing on abundance variability of Pacific saury (Cololabis saira) in the western North Pacific Ocean during 1982–2018. (10th November 2020) - Yatsu, Akihiko; Okamura, Hiroshi; Ichii, Taro; Watanabe, Kazuyoshi
Abstract: Pacific saury ( Cololabis saira ) has a 2‐year life span and age‐1 fish migrates from the central and western North Pacific to Japanese waters from summer to winter. To understand interannual abundance variability of Pacific saury in the North Pacific, we examined the extended Japanese standardized catch per unit effort (esCPUE) with generalized linear models (GLMs) during 1982–2018. Explanatory variables included proxies of total and non‐traditional fishing effort ( Ettl and Ent ) and environmental factors. Each environmental variable was averaged for years t ‐1 and t, corresponding to esCPUE in year t, as esCPUE represented two‐year classes. Ettl and Ent were averaged for years t ‐ 2 and t‐1, assuming fishing of year t affects biomass in year t + 1 . We compared four GLMs with different explanatory variables: (a) environmental factors only, (b) fishing effort (without interactions) only, (c) environmental factors and fishing effort (without interactions) and (d) environmental factors and fishing effort (with interactions, i.e., time‐varying effects). Explanatory variables of the best GLM in terms of AICc included the following: Ent with different effects between 1982–2015 and 2016–2018, sea surface water temperature (SST) of the Kuroshio Recirculation Area (KRA) in winter, North Pacific Gyre Oscillation (NPGO) in winter, Southern Oscillation Index in winter, and the biomass of Japanese sardine. The NPGO, a proxy of zooplankton abundance, and KRA‐SST may affect the early growth and survival rates of Pacific saury. We hypothesized the abundance variability of Pacific saury was driven by environmental factors and fishing, the latter of which more adversely affected since 2016.